Bond strength of reinforcing steel embedded in fly ash-based geopolymer concrete - Sarker, Prabir (Springer Netherlands, 2011)
Geopolymer concrete (GPC) is an emerging construction material that uses a by-product material such as fly ash as a complete substitute for cement. This paper evaluates the bond strength of fly ash based geopolymer concrete with reinforcing steel. Pull-out test in accordance with the ASTM A944 Standard was carried out on 24 geopolymer concrete and 24 ordinary Portland cement (OPC) concrete beam-end specimens, and the bond strengths of the two types of concrete were compared. The compressive strength of geopolymer concrete varied from 25 to 39 MPa. The other test parameters were concrete cover and bar diameter. The reinforcing steel was 20 mm and 24 mm diameter 500 MPa steel deformed bars. The concrete cover to bar diameter ratio varied from 1.71 to 3.62. Failure occurred with the splitting of concrete in the region bonded with the steel bar, in both geopolymer and OPC concrete specimens. Comparison of the test results shows that geopolymer concrete has higher bond strength than OPC concrete. This is because of the higher splitting tensile strength of geopolymer concrete than of OPC concrete of the same compressive strength. A comparison between the splitting tensile strengths of OPC and geopolymer concrete of compressive strengths ranging from 25 to 89 MPa shows that geopolymer concrete has higher splitting tensile strength than OPC concrete. This suggests that the existing analytical expressions for bond strength of OPC concrete can be conservatively used for calculation of bond strength of geopolymer concrete with reinforcing steel.